Unity and Multiplicity in Islamic Geometric and Calligraphic Expression: A Photographic and Visual Journey of Space in Nusantara Mosques - Nurhaya Baniyamin; Zumahiran Kamaruddin; Rajabi Abdul Razak (Universitas Indraprasta PGRI, 2019)
The paper describes how the experience and philosophy of Islamic unity and multiplicity are heightened through a photographic compilation of surface patterning; geometric and calligraphic in Mosques in the region. It then focuses on two mosques to highlight their particular contributions to achieved a contextualisation of such a universal aesthetic design and expression. Both masjid Negara Kuala Lumpur and the Istilal Mosque, Jakarta, represent key innovation, of prayer hall expression and decoration due to the contextualisation, and regionalization of essential geometric patterning, which departs from the usual stereotypical Islamic geometry to embrace and forward a Nusantara identity that resonates with minimalism and modernization in the industrialized world.